The Impact of AI on the Marketing Process - Koijam, Luckyson (Journal of Global Economy, Business and Finance, 2026)
Artificial Intelligence (AI) has emerged as a transformative force in the field of marketing, revolutionizing the way businesses understand, engage with, and cater to their customers. This article explores the multifaceted impact of AI in marketing, emphasizing its role in enhancing customer experiences, improving marketing strategies, and optimizing operational efficiency. By examining recent developments and case studies, this text illuminates AI's potential to reshape marketing practices, while also addressing the ethical and privacy considerations that come with its implementation.